"I aspire to look and feel healthy like the posts convey": engagement with fitness inspiration on social media and perceptions of its influence on health and wellbeing - Michelle Raggatt; Cassandra J. C. Wright; Elise Carrotte; Rebecca Jenkinson; Kate Mulgrew; Ivanka Prichard; Megan S. C. Lim (BMC, 2018)
Abstract Background Fitspiration is a popular social media trend containing images, quotes and advice related to exercise and healthy eating. This study aimed to 1) describe the types of fitspiration content that users access and how they engage with content, 2) investigate the disordered eating and exercise behaviours and psychological distress of individuals who access fitspiration, and 3) understand the perceived influence of fitspiration on health and wellbeing. Methods Participants who access fitspiration content were recruited via social media to complete a cross-sectional online survey. Participants' psychological distress was measured using the Kessler 10 Psychological Distress Scale (K10); disordered eating behaviours using the Eating Attitudes Test-26 (EAT-26); and compulsive exercise behaviours using the Exercise Addiction Inventory (EAI). Participants also answered a series of open-ended questions about their experiences with fitspiration. A descriptive statistical analysis was conducted for quantitative data. Responses to open-ended questions were analysed for key themes using an iterative process of open, axial and thematic coding. Results Participants (N = 180, 151 female, median age 23.0 years (IQR 19.0, 28.5)) most commonly accessed content posted by personal trainers and athletes (59.4%), posts tagged with the 'fitspiration' hashtag (53.9%) and posted by 'everyday' people (53.3%). Overall, 17.7% of participants were classified as high risk for an eating disorder, 17.4% reported very high levels of psychological distress, and 10.3% were at risk of addictive exercise behaviours. Participants described both positive and negative influences of engaging with fitspiration content. The influence on their health beliefs and behaviours was explained through four key themes: 1) Setting the 'healthy ideal', 2) Failure to achieve the 'ideal', 3) Being part of a community, and 4) Access to reliable health information. Conclusions Many participants reported benefits of fitspiration content including increased social support and access to health information. However, participants also reported that fitspiration content could negatively influence their wellbeing and perception of healthy goals. Content posted by relatable individuals or qualified experts was perceived as most trustworthy. Future research is needed to determine the individual and content-related factors associated with negative and positive fitspiration experiences.